Timing the Maltese business cycle: A historical perspective - Reuben Ellul (Central Bank of Malta, 2021)
Despite data limitations, formal methods can still be applied to identify business cycle turning points and hence date appropriately the Maltese business cycle. An extension of the official quarterly GDP time series to the 1970s allows for a historical view on dating the business cycle, leading to the identification of tentative set of recessionary episodes. In line with the business cycle literature, which suggests that multiple data ought to be considered when timing the business cycle, unemployment rate data are also considered. Findings with respect to developments in the labour market are also discussed. The study also highlights pitfalls in the timing of recessions in Malta, relating to problems in the estimation of national accounts, as well as the number of observations of the GDP time-series. This study represents a first step towards maintaining a chronology of Maltese business cycles by collating a dataset, analysing it and focusing on the statistical aspects of business cycles.
Keywords: C24; C25; E32; 330; Malta; business cycle; recessions